Design of a Super Twisting Sliding Mode Controller for an MR Damper-Based Semi-Active Prosthetic Knee - Assfaw, Dawit; Seid, Solomon (Frontiers in Robotics and AI, 2022)
A large number of transfemoral amputees living in low-income countries couldn’t access a much-needed prosthesis. Hence, affordable semi-active prosthetic knees are designed in recent years. As the swing phase of the gait cycle is unstable as compared to the stance phase, those designs couldn’t perfectly mimic this phase of a healthy human being. In contribution toward such a gap, this paper proposes modeling and design of a robust controller for magnetorheological (MR) damper-based semi-active prosthetic knee. A dynamic model representation for the swing phase of the single-axis knee is derived first. Subsequently, an MR damper valve model is developed. Then, a higher-order sliding mode controller is designed and evaluated for its stability and performance. The numerical simulation results show that the super twisting sliding mode controller improves the semi-active prosthetic knee's tracking efficiency. The design exhibited the finest performance providing low NRMSE as compared to previous designs. The robustness evaluation for this controller also showed its ability to continue providing excellent performance in the presence of disturbances.